The Effect of Hand Washing with Soap Education Using Puzzle Media on Hand Washing with Soap Behavior in Elementary School Age Children - Amelia Nur Indah Sari; Aida Novitasari; Ach. Arfan Adinata; Indriatie (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Clean and healthy living behavior by washing hands is an important effort to minimize the emergence of disease. However, many people, including children, do not know how to properly maintain hand hygiene. The aim of the research was to determine the effect of hand washing with soap education using puzzle media on the hand washing behavior with soap of elementary school aged children. The research used a pre-experimental design with a One Group Pretest-Posttest Design approach. The sample consisted of 56 students as the intervention group. Data analysis used the Wilcoxon Signed Ranks Test. The use of puzzle media has been proven to have an influence with a significance value of 0.000 < 0.005 on behavior in the domain of knowledge, attitudes and actions in elementary school age children. Teachers, health workers and the general public can provide education through puzzle media to children because it is interesting, easy to understand and affordable. INDEX TERMS : Education, Elementary School Age Children, Hand Washing with Soap, Puzzle